2022
DOI: 10.5194/aab-65-385-2022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fenugreek seed (Trigonella foenum-graecum) supplementation on the performance and milk yield characteristics of dairy goats

Abstract: Abstract. The use of fenugreek seed as a galactagogue has been investigated in ruminants. However, only a few studies have analyzed the effects of fenugreek seed on the milk fatty acid composition. To the authors' best knowledge, none of these studies have investigated the effects of fenugreek seed on milk volatile compounds. The objective of this study, which lasted 8 weeks, was to determine the effects of fenugreek seed supplementation on the performance, milk fatty acid profile, and milk volatile profile of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[65] Surprisingly, few studies have been done to understand the effects of fenugreek on lactation. Studies in dairy animals on milk yield have found conflicting results, [66][67][68] although fenugreek fed to dairy cows enhances milk unsaturated fatty acid concentration. [67] However, two studies in rats provide important insight.…”
Section: Effects Of Polyphenol-rich Botanicals On Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…[65] Surprisingly, few studies have been done to understand the effects of fenugreek on lactation. Studies in dairy animals on milk yield have found conflicting results, [66][67][68] although fenugreek fed to dairy cows enhances milk unsaturated fatty acid concentration. [67] However, two studies in rats provide important insight.…”
Section: Effects Of Polyphenol-rich Botanicals On Lactationmentioning
confidence: 99%
“…Studies in dairy animals on milk yield have found conflicting results, [66][67][68] although fenugreek fed to dairy cows enhances milk unsaturated fatty acid concentration. [67] However, two studies in rats provide important insight. Rats lactationally challenged by artificially increased litter size and fed fenugreek (1 g kg −1 BW d −1 ), have greater milk production and pup growth with no deleterious effects on metabolism.…”
Section: Effects Of Polyphenol-rich Botanicals On Lactationmentioning
confidence: 99%
“…Other results revealed a significant effect of herbal supplements on the concentration of biologically active substances, such as apigenin, apigenin 7-glucoside and chlorogenic acid, in goat serum [13]. Another interesting result related to modifying goat milk's fatty acid profile by adding fenugreek grain to goats' diet [14]. Phytobiotics as pure botanicals, such as thymol and vanillin, when used in the nutrition of dairy goats, have confirmed a positive effect on milk yield and animal metabolic and immune status [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fenugreek (foenum Trigonella -graecum) from the family Fabaceae, order Leguminosae, is self-pollinating with a forked stem and trifoliate leaves bearing white flowers that produce golden yellow seeds [4]. Recent studies have shown that using fenugreek as a nutritional supplement led to an increase in milk production and efficiency without any harmful effects on the health of lactating goats, thus increasing the profits of animal farms [5,6]. Fennel )Foeniculum vulgare( is an aromatic plant belonging to Apiaceae family.…”
Section: Introductionmentioning
confidence: 99%